How important are shocks to the elasticity of aggregate labor supply for business cycle fluctuations? - Aleksandar Vasilev (Economics and Econometrics Research Institute (EERI), 2022)
Stochastic shocks to aggregate labor supply elasticity are introduced into a real-business-cycle setup augmented with a detailed government sector. The model is calibrated to Bulgarian data for the period following the introduction of the currency board arrange-ment (1999-2018). The quantitative importance of a stochastic aggregate labor supply elasticity parameter is investigated for the magnitude of the cyclical fluctuations in Bulgaria. The quantitative effect of such a stochasticity increases the variability of hours, and lowers the correlation between hours and wages, and thus is found to be quantitatively important for the labor market aspect of business cycles.
Keywords: E24; E32; 330; Business cycles; stochastic aggregate labor supply elasticity; Bulgaria